Budget Refocusing And Reallocation Strategies: Rescuing Indonesia's Tourism Sector Amid The COVID-19 Pandemic - Andy Mulyana; Nadhira Hardiana; Noorina Hartati; Ni Wayan Marsha Satyarini (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The COVID-19 pandemic has forced the Indonesian Government to refocus and reallocate the budget to overcome the economic and social impacts that have arisen. The tourism sector is one of the most affected sectors, so it requires special attention in budget allocation policies. This research aims to analyze the phenomenon of budget refocusing and reallocation in the tourism sector and the challenges faced in its implementation. Using a qualitative approach with a case study method, this research collected data from in-depth interviews with key stakeholders in the tourism sector, as well as documentation from various secondary sources. Data analysis was carried out using the interactive analysis model from Miles and Huberman, which consists of three main components: data display, data reduction, and conclusion drawing/verification. The research results show that the refocusing and reallocation of budgets implemented by regional governments, especially in the Special Region of Yogyakarta (DIY), has had a significant impact in supporting the tourism sector. However, challenges remain, including the need for innovation according to current tourism trends, hygienic tourism infrastructure and facilities, as well as improving tourism information and promotion networks. By using the Resource Based View (RBV) and Actor-Network Theory (ANT) approaches, this research provides insight into how resources and interactions between actors can be utilized to achieve competitive advantage and maintain sustainable performance in the tourism sector. This research also provides policy recommendations that can be implemented to support the recovery and sustainability of the tourism sector in the future.